2019
DOI: 10.2147/dmso.s234243
|View full text |Cite
|
Sign up to set email alerts
|

<p>Is PCSK9 Associated with Plasma Lipid Levels in a Sub-Saharan African Population of Patients with Obesity and Type 2 Diabetes?</p>

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a key regulator of circulating LDL cholesterol. There are inconsistent data in some populations concerning the association between PCSK9, LDL and CRP. The emerging importance of the inhibition of PCSK9 for the treatment of hypercholesterolemia warrants investigations in different populations. The aim of this study from a Sub-Saharan African population was to evaluate the association between PCSK9 and hs-CRP levels and plasma lipid levels in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
5
1
Order By: Relevance
“…They also reported no significant relationship between PCSK9 levels and BMI in both boys and girls, which is similar to our findings [18]. On the opposite, higher BMI was associated with higher PCSK9 levels in an obese Sub-Saharan African adult population [33]. While in the present report no significant relationship was noted between PCSK9 and BMI, it is noteworthy that in our previously published results on the same cohort, BMI was significantly correlated with non-HDL-C and TG [23].…”
Section: Discussionsupporting
confidence: 89%
“…They also reported no significant relationship between PCSK9 levels and BMI in both boys and girls, which is similar to our findings [18]. On the opposite, higher BMI was associated with higher PCSK9 levels in an obese Sub-Saharan African adult population [33]. While in the present report no significant relationship was noted between PCSK9 and BMI, it is noteworthy that in our previously published results on the same cohort, BMI was significantly correlated with non-HDL-C and TG [23].…”
Section: Discussionsupporting
confidence: 89%
“…We also did not find any relationship between PCSK9 and BMI. Higher BMI score was associated with higher levels of PCSK9 in a Sub-Saharan African Population of Patients with Obesity [ 20 ], a finding that was not also observed in the current study. On multivariate analysis, high levels of PCSK9 were significantly correlated with TG, a result similar to that of Lakoski et al [ 16 ].…”
Section: Discussioncontrasting
confidence: 43%
“…Elevated levels of circulating PCSK9 have also been associated with increased LDL-C, TG [ 16 ] and worse cardiovascular outcomes [ 17 ]. PCSK9 levels varies according to gender, age, and BMI, with higher levels in women compared to men [ 16 , 18 ], postmenopausal vs. premenopausal women [ 16 , 18 , 19 ], and in subjects with a higher BMI [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in obese people, normal LDL-C levels may suggest that increased adipocytes are maintaining cholesterol homeostasis. In addition, proprotein convertase subtilisin/kexin type 9 (PCSK9) is positively associated with BMI and LDL-C levels, which confirms the association between BMI and LDL-C [ 36 , 37 ]. It has been reported that PCSK9 concentrations are correlated with age, gender, MS, and menopausal status, which may lead to alterations in the linear association [ 38 ].…”
Section: Discussionmentioning
confidence: 81%